BRIDGING CULTURES: ENGLISH LANGUAGE LEARNING FROM PESANTREN TO AMERICA - Zulfi Zumala Dwi Andriani (Universitas Kuningan, 2024)
This article is a narrative inquiry research which focus on a young female santri named Aisya (pseudo name), who got the MORA Overseas Student Mobility Award (MOSMA) for six months in Buffalo University New York, USA. the research focus on analyzing Aisyaâs life story in relation to her English learning strategy and lensed from three perspective; English as linguistic capital (Bourdieu, 2018), English as social investment (Peirce, 1995) and creative discursive agency (Collins, 2000). the data collected through in depth and unstructured interview for three time through zoom meeting, the supporting data is also in the form of Aisya personal essay related to her goal of life. The research revealed that mastering English instead of coming from internal motivation, it also much influenced by social agent such as family, Kyai and Pesantren. having ability of English is also could activate the social investment which then transform it into many opportunities for creative discursive agency such as getting high score of TOEFL and acquiring scholarship to America as like Aisya had. Pedagogically, it resulted some implications such as the importance of providing more student-centered approach in classroom in signifying Â the diversity of each student's background can be accommodated by the teacher, thereby creating motivation to learn English. For pesantren, it suggested to have strong commitment instead of teaching religious knowledge but also on developing foreign language namely English. Keywords [English Language, Pesantren, Narrative Inqury, social investment]